„Ближайшая станция европейской культуры…”: полонофилия 60-х годов - Vorontsova, Kristina (Studia Rossica Posnaniensia, 2019)
The article attempts to trace the sources of “polonophilia” in the Soviet culture of the sixties and to consider the strategies of the representation of the Polish text in Russian literature after the Khrushchev Thaw on the material of Stanislav Kunyaev, Boris Dubrovin and Emil Janvarev’s poetry. The special influence on the formation of the geo-cultural image of the Polish People’s Republic in this period is discussed in the context of Polish cinema (in particular Andrzej Wajda’s film Ashes and Diamonds).